ANALISIS PENDAPATAN USAHATANI TANAMAN PADI’SAWAH PASANG SURUT (Oryza sativa L) DI DESA PEMURUS KECAMATAN ALUH-UH’KABUPATEN’BANJAR PROVINSI’ KALIMANTAN’SELATAN - Wasdiyanta; Zuraida (Fakultas Pertanian UVAYA Banjarmasin, 2021)
This study aims to determine technically the cultivation of rice plants and technically to determine the costs, production, prices and income of rice farming. Village sampling was carried out by purposive sampling, namely Pemurus Village (water overflow type B) then farmer sampling was carried out intentionally or purposive random sampling. The result of this research is the average cost of Rp. 3,813,577.70, the average product size is 2,073.5 kg and the average income is Rp. 6,553.922.30